2020
DOI: 10.1002/admi.201901521
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Elucidation of Grain Boundary Behavior in All‐Inorganic Halide Perovskites by Scanning Probe Microscopy

Abstract: All‐inorganic halide perovskite (AIHP) is becoming one of the most promising generation materials of perovskite photovoltaics for commercialization due to its thermodynamic stability and soared efficiency. Depending on material properties, grain boundary (GB) has detrimental or beneficial effect on device photovoltaic performance. However, less attention is paid to GB behavior in AIHPs. Herein, it is concluded that the microscopic GBs are the major sites for photocarrier generation and transport, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Film crystallinity and morphology when varying A and X site composition are critical in achieving photostability, since photoinduced phase segregation necessarily requires the migration or diffusion of the halide anions. , It is well accepted that ionic migration is mediated and accelerated along grain boundaries. Suppression of photoinduced halide phase segregation has been identified by A-cation alloying, B-cation alloying, and improving crystallinity. , However, few studies provide the detailed differentiation between ion migration and phase segregation under illumination. Especially, the time-dependent changes of the hybrid perovskite optical and electrical response to corresponding changes of device-level performance metrics are often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Film crystallinity and morphology when varying A and X site composition are critical in achieving photostability, since photoinduced phase segregation necessarily requires the migration or diffusion of the halide anions. , It is well accepted that ionic migration is mediated and accelerated along grain boundaries. Suppression of photoinduced halide phase segregation has been identified by A-cation alloying, B-cation alloying, and improving crystallinity. , However, few studies provide the detailed differentiation between ion migration and phase segregation under illumination. Especially, the time-dependent changes of the hybrid perovskite optical and electrical response to corresponding changes of device-level performance metrics are often ignored.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Confocal photoluminescence (PL) measurements suggest that these phases form at grain boundaries (GB), where current–voltage curve hysteresis is shown to be increased, further indicating ionic displacement and trap site formation. 6 , 10 12 On the other hand, Li et al have observed higher conductivity at GBs via conductive atomic force microscopy (AFM) arguing that GBs act as conduction pathways rather than recombination sites. 13 Cesium-incorporated perovskites offer an attractive solution, as they have been shown to constrain effects such as phase segregation while maintaining high efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…In typical I-Br mixed-halide perovskites, iodide and/or bromide rich phases tend to form under prolonged illumination 8,9 . Confocal photoluminescence (PL) measurements suggest that these phases form at grain boundaries (GB), where current-voltage curve hysteresis is shown to be increased, further indicating ionic displacement and trap site formation 6,[10][11][12] . On the other hand, Li et al have observed higher conductivity at GBs via conductive atomic force microscopy arguing that GBs act as conduction pathways rather than recombination sites 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Systemes, Pawtucket, RI, USA) to simulate the effects of pressure application on multilayered PSCs structures with pre-existing interfacial defects. The models assume that, in a model PSC structure, there are pre-existing grain-boundary cracks and voids 11,12,21,23,24 , as well as interfacial defects (voids and interfacial cracks) before pressure application ( Fig. 5a).…”
Section: Moderate Pressure Closes Voids and Cracksmentioning
confidence: 99%